Resepsi Khalayak Mengenai Berita Kekerasan Seksual pada Media Online Kompas.com - Sarah Siti Saryati; Arba'iyah Satriani (UNISBA Press, 2024)
Abstract. This research is based on patriarchal cultural practices that still persist issue of protecting women and children as a rationale, referring to the principles of gender equality and the existence of feminism as the basis of struggle. In this research, it was found that news about KBGO is still a topic that is widely discussed in online media such as Kompas. The hypothetical position of a reader after reading an article reporting on Online Gender-Based Violence on Kompas.com is relatively positive, namely that the discussion regarding Online Gender-Based Violence in the article is considered to be quite balanced, in favor of women, but it is complained that it is not very educative because it does not show any risks that occur. Abstrak. Penelitian ini dilatarbelakangi oleh praktik budaya patriarki yang masih mempertahankan isu perlindungan perempuan dan anak sebagai landasan pemikirannya, mengacu pada prinsip kesetaraan gender dan eksistensi feminisme sebagai landasan perjuangan. Dalam penelitian ini ditemukan bahwa pemberitaan tentang KBGO masih menjadi topik yang banyak diperbincangkan di media online seperti Kompas. Posisi hipotetis pembaca setelah membaca artikel pemberitaan Kekerasan Berbasis Gender Online di Kompas.com relatif positif, yaitu pembahasan mengenai Kekerasan Berbasis Gender Online dalam artikel tersebut dinilai cukup berimbang, berpihak pada perempuan, namun dikeluhkan kurang mendidik karena tidak menunjukkan adanya risiko yang terjadi.